2018
DOI: 10.3390/ma11091673
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of an Electrospun PHA/Graphene Silver Nanocomposite Scaffold for Antibacterial Applications

Abstract: Many wounds are unresponsive to currently available treatment techniques and therefore there is an immense need to explore suitable materials, including biomaterials, which could be considered as the crucial factor to accelerate the healing cascade. In this study, we fabricated polyhydroxyalkanoate-based antibacterial mats via an electrospinning technique. One-pot green synthesized graphene-decorated silver nanoparticles (GAg) were incorporated into the fibres of poly-3 hydroxybutarate-co-12 mol.% hydroxyhexan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…The results showed that the survival ratio of E. coli and S. aureus decreases exponentially with increasing bSNPs content. A similar report was demonstrated by Mukheem et al [46], where PHA/Graphene Silver nanocomposite showed reduction of S. aureus and E. coli as compared to bare PHA in 2 h of time. In the present study, the maximum antibacterial activity (about 94.7 and 92% growth inhibition for E. coli and S. aureus , respectively) was attained with 2.0 wt % loading which could be because of the larger size of bSNPs providing active surface area reactivity.…”
Section: Resultssupporting
confidence: 86%
“…The results showed that the survival ratio of E. coli and S. aureus decreases exponentially with increasing bSNPs content. A similar report was demonstrated by Mukheem et al [46], where PHA/Graphene Silver nanocomposite showed reduction of S. aureus and E. coli as compared to bare PHA in 2 h of time. In the present study, the maximum antibacterial activity (about 94.7 and 92% growth inhibition for E. coli and S. aureus , respectively) was attained with 2.0 wt % loading which could be because of the larger size of bSNPs providing active surface area reactivity.…”
Section: Resultssupporting
confidence: 86%
“…1B) con rmed the characteristic peaks for GO that were observed at 3440 (OH stretching), 1728 (C = O stretching), 1623 (C = C stretching) and 1041 cm -1 (C-O stretching). The presence of oxygen-containing functional groups such as hydroxyl, carboxyl and epoxy proved the successfully oxidation process of graphite powder to GO (Mukheem et al, 2018). Besides, after addition and reduction of silver ions (Ag + ), the -OH groups were stretched and shifted from 3404 to 3438 cm − 1 that con rm the interactions between Ag + and/or AgNPs and the oxygenated groups on the rGO.…”
Section: Characterization Of the Nanocompositementioning
confidence: 92%
“…There is also a subtype of PHAs that includes copolymers of scl-mcl PHAs of 4 to 12 carbon atoms ( Hazer and Steinbuchel, 2007 ). PHA-based nanoparticles have been used to deliver biomolecules for anticancer ( Lu et al, 2011 ; Fan et al, 2018 ; Radu et al, 2019 ) and antibacterial applications ( Castro-Mayorga et al, 2014 , 2016 ; Mukheem et al, 2018 ). Nanocarriers fabricated from PHA−grafted copolymers have also been developed for efficient siRNA delivery ( Zhou et al, 2012 ); these formulations are safe siRNA carriers for gene therapy.…”
Section: Nanomedicinementioning
confidence: 99%